2017
DOI: 10.1126/science.aan0221
|View full text |Cite
|
Sign up to set email alerts
|

The biology of color

Abstract: Coloration mediates the relationship between an organism and its environment in important ways, including social signaling, antipredator defenses, parasitic exploitation, thermoregulation, and protection from ultraviolet light, microbes, and abrasion. Methodological breakthroughs are accelerating knowledge of the processes underlying both the production of animal coloration and its perception, experiments are advancing understanding of mechanism and function, and measurements of color collected noninvasively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
524
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 604 publications
(533 citation statements)
references
References 98 publications
4
524
0
5
Order By: Relevance
“…For instance, several studies have consistently identified coding changes as well as putative regulatory differences in the gene agouti signalling protein (ASIP) between birds with melanic and non-melanic plumage patches [1,14,18,28]. Our assay identified 72 SNPs within 50 kb of the ASIP coding region, but none were highly differentiated between myrtle and Audubon's warblers (average F ST in this region ¼ 0.02, lower than the genome-wide average of 0.045).…”
Section: (B) Candidate Genes and Functional Interpretationsmentioning
confidence: 81%
See 1 more Smart Citation
“…For instance, several studies have consistently identified coding changes as well as putative regulatory differences in the gene agouti signalling protein (ASIP) between birds with melanic and non-melanic plumage patches [1,14,18,28]. Our assay identified 72 SNPs within 50 kb of the ASIP coding region, but none were highly differentiated between myrtle and Audubon's warblers (average F ST in this region ¼ 0.02, lower than the genome-wide average of 0.045).…”
Section: (B) Candidate Genes and Functional Interpretationsmentioning
confidence: 81%
“…Coloration is among the most conspicuous phenotypes to differ among closely related species [1,2]. Using genetic crosses, association studies have identified a number of key genes involved in pigmentation pathways that give rise to such colour differences [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…[273,274] In particular, intricate optical structures deliver specialized signals that are processed into information by complex visual systems, the eyes. [275,276] The cuticle exoskeleton of certain insects contains ordered, quasi-ordered or disordered nanostructures that reflect light in particular wavelength ranges and can produce vibrant colors, while cuticle on the exterior of other insects forms nanostructured layers that prevent light reflection entirely, rendering them transparent. Mechanisms to manipulate light have developed alongside those to detect it; the surface of some insect eyes is patterned with nanoscale features that promote efficient light transmission and also act as a hydrophobic deterrent for visionblocking condensation (Section 4).…”
Section: Sensing and Manipulation Of Lightmentioning
confidence: 99%
“…[277] Numerous recent reviews discuss the physical aspects of insect displays, [273,[277][278][279][280][281][282][283][284][285][286] as well as their function in animal communication. [275,276,287] In general, there are two main classes of animal coloration: pigmentary coloration due to the wavelength-selective light absorption by chemical dyes and structural coloration due to the interaction of incident light with ordered, quasi-ordered or disordered nanostructures causing interference. [277,288,289] Both coloration mechanisms feature unique optical properties that can combine in nontrivial ways and modulate optical properties with potential applications ranging from displays, to brilliant durable paints, to adaptive camouflage and transparent materials.…”
Section: Mechanisms Of Color Productionmentioning
confidence: 99%
See 1 more Smart Citation